DISTRIBUTION AND CHARACTERISTICS OF HEAD INJURY AND REFERRAL NUMBER AT DR H. ANDI ABDURRAHMAN NOOR GENERAL HOSPITAL, TANAH BUMBU, SOUTH BORNEO, INDONESIA - Komang Werdhi Sentosa; Ani Rahmawati; Daldy Arianda; Ardik Lahdimawan; Agus Suhendar (Neurologico Spinale Medico Chirurgico, 2018)
Background: Head injury (HI) has been one among leading causes of morbidity and mortality worldwide especially in the peripheries area. In South Borneo, 9.4% of trauma cases was a head injury. Especially, Tanah Bumbu Regency, one of peripheries area in South Borneo ranks third for head injuries after Tabalong and Tanah Laut Regency in 2007. Objective: The aim of this study was to describe the characteristics of head injury patient and referral number at Dr. H. Andi Abdurrahman Noor general hospital. Methods: All head injury patients admitted to the emergency department (ED) of Dr. H. Andi Abdurrahman Noor general Hospital in a one-year period (2017) were registered in this retrospective study. Using the total population sampling method,413 cases of head injury during the period were included as a subject of study. Result: This study showed that mild head injury was the most cases of head injury with 325 cases (78.2%). 61 patients were referred to a higher trauma center in 2017. Head injury was most common in 11‑20 years old age group. Men also had higher incident rate compared to women (2:1). Most of the patients were a nonstate employee. Head injury is commonly caused by traffic accident. Conclusion: This study shows that characteristics of HI in the peripheries area such Tanah Bumbu regency are no different from other countries. Our findings suggest that several prevention steps should be taken to reduce the number of head injury based on the distribution and characteristics of head injury sustainers.